Matrix metalloproteinase-2 enhances platelet deposition on collagen under flow conditions - Guglielmini, Giuseppe; Appolloni, Viviana; Momi, Stefania; Groot, Philip G. de; Battiston, Monica; Marco, Luigi de; Falcinelli, Emanuela; Gresele, Paolo (Thrombosis and Haemostasis, 2016)
Platelets contain and release matrix metalloproteinase-2 (MMP-2) that in turn potentiates platelet aggregation. Platelet deposition on a damaged vascular wall is the first, crucial, step leading to thrombosis. Little is known about the effects of MMP-2 on platelet activation and adhesion under flow conditions. We studied the effect of MMP-2 on shear-dependent platelet activation using the O’Brien filtration system, and on platelet deposition using a parallel-plate perfusion chamber. Preincubation of human whole blood with active MMP-2 (50 ng/ml, i. e. 0.78 nM) shortened filter closure time (from 51.8 ± 3.6 sec to 40 ± 2.7 sec, p< 0.05) and increased retained platelets (from 72.3 ± 2.3 % to 81.1 ± 1.8 %, p< 0.05) in the O’Brien system, an effect prevented by a specific MMP-2 inhibitor. High shear stress induced the release of MMP-2 from platelets, while TIMP-2 levels were not significantly reduced, therefore, the MMP-2/TIMP-2 ratio increased significantly showing enhanced MMP-2 activity. Preincubation of whole blood with active MMP-2 (0.5 to 50 ng/ml, i.e 0.0078 to 0.78 nM) increased dose-dependently human platelet deposition on collagen under high shear-rate flow conditions (3000 sec-1) (maximum +47.0 ± 11.9 %, p< 0.05, with 50 ng/ml), while pre-incubation with a MMP-2 inhibitor reduced platelet deposition. In real-time microscopy studies, increased deposition of platelets on collagen induced by MMP-2 started 85 sec from the beginning of perfusion, and was abolished by a GPIIb/IIIa antagonist, while MMP-2 had no effect on platelet deposition on fibrinogen or VWF. Confocal microscopy showed that MMP-2 enhances thrombus volume (+20.0 ± 3.0 % vs control) rather than adhesion. In conclusion, we show that MMP-2 potentiates shear-induced platelet activation by enhancing thrombus formation.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Matrix metalloproteinases; platelet adhesion; shear stress; TIMP-2